The Intersection of Traditional and Modern Terminology as a Barrier in Understanding the Administrative Process - V. A. Zyuzin (Сибирское юридическое обозрение, 2021)
At present, in connection with the constitutional reform carried out in the Russian Federation, the process of reconciliation of the basic categories of administrative law with the Constitution is actively underway. In parallel, in the scientific community of specialists in administrative law and process, there has long been a request for the harmonization of views and concepts for the formation of modern administrative procedural legislation. Such a serious scientific task can be successfully solved only by relying on the letter and spirit of the country's fundamental law as the only indisputable starting point for doctrinal provisions. The catalyst for many years of discussion about the boundaries and essence of the administrative process was the adoption in 2015 of the Code of Administrative Proceedings of the Russian Federation. After the enactment of this code in scientific circulation, the categories of “judicial administrative law” and “judicial administrative process” are actively used, which brings the domestic doctrine closer to the theory of developed foreign countries. However, even in the absence of a law in Russia that defines the legal foundations of an extrajudicial administrative process, one should not forget that the majority of modern representatives of science recognize the existence of an extrajudicial administrative process in the Russian Federation. We are talking about the widest range of administrative cases - about the activities of administrative-public bodies to resolve administrative matters under their jurisdiction, both of a regulatory and protective nature, controversial and indisputable. In this situation, we believe that it is required to conduct a scientific analysis of the terminology used in Russia to study the essence of the administrative process. The article makes an attempt, taking into account foreign and domestic doctrine, to study numerous definitions for suitability for the formation of a uniform understanding of the administrative process in the Russian Federation. The work, in particular, explores the understanding of public administration and administrative justice, compares the content of the terms “administrative jurisdiction” and “administrative procedures” in Russia and in foreign countries. Based on the results of the analysis, it is concluded that the least controversy is caused by the use of the term “administrative proceedings” in relation to out-of-court proceedings and “administrative proceedings” to the judicial trial hearings.